Industrial Relations In The Digital Sharing Economy: A Critical Review of Labor Informalization and Social Partnership Relations - Kurniawan, Fuat Edi (RMPI-BRIN, 2020)
This study provides a critical analysis of digital transformation which not only creates new patterns in production, distribution, and consumption but also has implications for power. Various issues have yet to be responded to thoroughly by policymakers to have allowed the new labor relations created in the digital sharing economy to develop quickly and become fragile, especially for laborers. In this article used a qualitative method with the desk study approach, by collecting data and information through examinations, analyzing information data using secondary data. This data is in the form of books, journals, workforce data from BPS (Statistics Indonesia), supporting data from related institutions, laws and regulations related to work, reports and literature studies. The results of this study show the emergence of an online transportation based digital platform which has opened new job opportunities, on the other hand, the industrial relation formed are only based on “virtual agreement”. The social partnership relations that exist between business/industry players and workers also give rise to new anomalies. This relation obscures the rights and protection of laborers who are unknowingly experiencing exploitation. Digital platform businesses cover the practice of labor exploitation within the rhetorical frame of freedom, flexibility, and partnership. It is the company that is at the peak of power, with control over technology, capital, and access. This study provides input to stakeholders, both government and digital industry, that digital developments should be able to be utilized in influencing social transformation that builds industrial optimism, technology, and empowers society more broadly. State authority and private power need to be integrated to act and be socially responsible. New findings in this study are on aspects digital-based industries cannot be separated from the process of commercialization and the massification of modern capitalism. Lack of regulations that become safety nets makes the labor’s position vulnerable and prone to being exploited. The industrial relation of social partnerships, and the absence of regulations governing the work of the informal sector, especially on the digital online transportation platform, creating new anomalies and problems for the labor.